New Strategic Education Management Paradigms in the Digital Transformation Context; A Literature Review - Puja Chamellia Putri; Zihori Maulida (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
Digital transformation in higher education has introduced substantial changes in governance, instructional processes, and institutional strategies, highlighting the need for a comprehensive understanding of its implications for strategic educational management. This study aims to examine how digital transformation influences managerial paradigms within higher education institutions. A qualitative approach was employed using a literature review design that examined empirical studies, qualitative research, quasi-experimental work, and systematic reviews published within the last decade. Data were analyzed thematically to identify recurring patterns across the literature. The findings indicate that digitalization strengthens data-driven management practices, enhances instructional effectiveness through LMS, hybrid learning, and learning analytics, and drives structural changes in institutional governance. Nevertheless, challenges such as limited digital competence, issues of data ethics and privacy, and uneven organizational readiness remain significant barriers. The study concludes that digital transformation holds considerable potential to improve management quality and learning processes yet requires comprehensive institutional strategies to ensure sustainable implementation. These findings offer meaningful contributions to the development of adaptive educational management in the digital era.